Storage Reliability and Temperature Increment with Tilted Free Layer Magnetization in Nanopillars for Spin Torque Magnetic Memory - Chayada Surawanitkun" (Science Faculty of Chiang Mai University, 2019)
Recently, the temperature increment in magnetic tunnel junction (MTJ) nanopillars with relevant current induced magnetization switching for spin transfer torque magnetic random access memory (STT-MRAM) has become interesting because it affects the reliability of devices. In this work, the magnetic stability and the temperature rise in the MTJ nanopillar during the switching process at pulse durations of less than 1 ns were explored with tilted magnetization in the free layer (FL). The thermal simulation was performed by the 3D finite element method. The results indicate that the increase of the initial angle between the magnetization vector and the major axis in the FL, , can reduce the temperature increment in the device and the risk for the magnetic damage impacting the storage stability. In addition, it was found that the altered temperature during the switching process is proportional to the square of . Thus, the reliability of the high-density STT-MRAM can be improved by tilting the FL magnetization in MTJ devices.